Experimental Investigation on the Cleaning Effect and Influence Rule of Hydrogen Peroxide–Acetic Acid on Lead–Bismuth Eutectic Alloy - Huang, Xi; Pang, Bo; Zhou, Xuelong; Yin, Yuan (Frontiers in Energy Research, 2021)
During the refueling process of Lead-bismuth eutectic (LBE) cooled fast reactors, lead-bismuth alloy can easily adhere to the surface of the fuel rod clads when spent fuel assemblies are unloaded from the reactor core. For some designs, the lead-bismuth alloy attached on the spent fuel rods will be cleaned via physical or/and chemical methods prior to their transportation, storage and reprocessing. In the article, the cleaning effect of a washing lotion composed of 30%-hydrogen peroxide (H2O2) aqueous solution and concentrated acetic acid (CH3COOH) as the main components on lead-bismuth eutectic alloy (LBE) was experimentally investigated. By adjusting composition ratio of the washing lotion and the reaction temperature, the law of their influence on the cleaning effect of LBE was obtained. An optimal washing lotion composition of 30 Vol% hydrogen peroxide aqueous solution as oxidant, 40 Vol% concentrated acetic acid as acid and 30 Vol% ultrapure water as solvent was proposed based on experimental investigation. The optimal working temperature range were also obtained. The reaction product was characterized with XRD analysis, in order to understand the reaction mechanism. The composition of the released gas (even in a slight amount) was also analyzed with gas chromatography and the hydrogen concentration was found to be lower than the detection limit of the gas chromatography (10 ppm). Consequently, the risk of possible hydrogen explosion is concluded to be extremely small and no special treatment will be required also in a large-scale industrial platform. Furthermore, corrosion degree of the washing lotion on austenitic stainlesssteel components was also tested and was found to be negligibly small.